A strategic recovery of value-added monomer from polycarbonate waste through catalytic pyrolysis on ultra-high porous MgO - Yang, Wooyoung; Choi, Doeun; Yu, Hak Ki; Jung, Sungyup; Lee, Jechan (Journal of Environmental Management, 2025)
The huge generation of plastic waste has become significant environmental problem. For environmentally sustainable plastic waste management, thermochemical recycling of widely used plastic waste such as polyethylene, polypropylene, polystyrene, and polyethylene terephthalate have vigorously studied. However, development of proper recycling process for other types of plastic waste is required. In this study, a thermo-catalytic treatment was applied for recovery of value-added monomers and gaseous products from polycarbonate (PC). The systematic study investigating the relationships between pyrolysis conditions (temperature, atmospheric gas, the presence of catalyst) and yield of value-added products was performed. To make the thermochemical process environmentally benign and more efficient, carbon dioxide (CO2) was used as an atmospheric gas in comparing to inert gas (N2). When CO2 was introduced, the yield of PC monomer, bisphenol A (BPA), was nearly doubled at 600 °C. At higher temperature, BPA yield decreased with the increased yield of gaseous products. Because CO2 was the major gaseous product, BPA recovery from the PC pyrolysis was the useful approach in PC disposal practice. To improve BPA yield from PC pyrolysis, two MgO catalysts were utilized (medium porosity MgO-1 and ultrahigh porosity MgO-2). Catalytic pyrolysis under CO2 environment increased BPA yield from 12.8 (pyrolysis without catalyst under N2) to 25.6 (MgO-1) and 30.5 wt% (MgO-2) at 600 °C. High porosity MgO catalyst was more effective in BPA production, and the catalyst deactivation was not shown for 4 consecutive reactions. This study informs that MgO catalyst and CO2 flow gas more than doubled the BPA yield from pyrolysis of PC in reference to conventional pyrolysis system (non-catalytic under N2).
Keywords: Bisphenol A; Bisphenols-A; Catalytic pyrolysis; Circular economy; Gaseous products; MgO; MgO catalyst; Plastics waste; Waste valorizations; ]+ catalyst; Carbon Dioxide; Catalysis; Magnesium Oxide; Plastics; Polycarboxylate Cement; Porosity; Pyrolysis; Recycling; Waste Management; Circular economy; MgO catalyst; Polycarbonate; Pyrolysis; Waste valorization